If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
28-((12*x)/4) = -8*x-(12/10) // + -8*x-(12/10)
12/10-((12*x)/4)-(-8*x)+28 = 0
8*x-3*x+12/10+28 = 0
5*x+146/5 = 0 // - 146/5
5*x = -146/5 // : 5
x = -146/5/5
x = -146/25
x = -146/25
| 53/5+4/5 | | 1-2.9=-3.6 | | 6.2x-4+x-1.2= | | 17-44=3(x-1)-6 | | 7j+11=14 | | 2x=4x-14.2 | | 15x-16=29+12x | | 27-3(9)+(7-4)b=24b | | 5t-4+3t=4(2t-1) | | x+x*0.12=6273.53 | | -7(x+2)-16=18+1 | | X+(2x-3)=72 | | 3+(15-1)(-4/3) | | 5y-2=29-4y | | 6=6+y | | 5(-3+7x)=-330 | | x+x*0.09=1000 | | 2(0.3r+1)=24 | | x-1/3=4/3 | | 5x+1=43-2x | | 2x^2+5x+6=x^2 | | 21x-16y=120 | | 10x-42+17x=13+14 | | .0855t^2-.916t+1.737=0 | | 8+2t-2=7t+8-4t | | 3(X+2)(X+2)+16(X+2)+5= | | 3+(5x-6/4) | | 3mx-9y=2(m+2b) | | x-7=144 | | 4s^2+16s-as-4a= | | 2/3(3/5) | | (5/6)t+4=(1/6)t-2 |